Reformasi Kualitas Pelayanan Publik di Indonesia - Risa Miliah; Yulia Kusuma (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
Bureaucratic reform is a process of renewal by using the transformation of the system or bureaucratic order in a better direction. In this study using secondary data collection methods in which this method collects data by examining books, scientific papers and documents which are certainly related to the problem of the researcher. The results of research on the impact of reduced performance in government organizations show that in 2010-2014 it has the same level every year, while for 2015-2019 it has increased in 2016.